Building Resilience Through Sport in Young People With Adverse Childhood Experiences - Norris, Gareth; Norris, Heather (Frontiers in Sports and Active Living, 2021)
Interventions focused on young people at risk of anti-social and criminal behaviour frequently involve physical exercise and/or participation in sporting activities as a primary vehicle to bring about behavioural change in both the short to medium term (Hughes, et al., 2018). Anecdotal evidence suggests that sporting activities positively influence individual well-being alongside a sense of purpose and belonging centred around sporting clubs and activities. Empirically, participation in sport has been identified as a key resilience factor for young people with numerous Adverse Childhood Experiences (ACEs) and investment and policy initiatives target investment in these opportunities (Bellis, et al., 2018). However, the psychological mechanisms which underpin these improvements in well-being and building of resilience are less clearly articulated. This article will review current and developing research in this field to synthesise future applications of sport-related interventions with young people, with a particular emphasis on furthering understanding of the pathways to capacity building at individual and community level which sport and exercise can generate.